If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + -9) = 29 Reorder the terms: 3(-9 + 4x) = 29 (-9 * 3 + 4x * 3) = 29 (-27 + 12x) = 29 Solving -27 + 12x = 29 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 12x = 29 + 27 Combine like terms: -27 + 27 = 0 0 + 12x = 29 + 27 12x = 29 + 27 Combine like terms: 29 + 27 = 56 12x = 56 Divide each side by '12'. x = 4.666666667 Simplifying x = 4.666666667
| 4x^3+12x^2+16=0 | | 3c+47=9c+41 | | 4(5)+y=24 | | 100y-2x=0 | | 15b=7b+40 | | 3p-1-2x+9=0 | | 19t+31=2t+65 | | r^2=88 | | 6h+8=26 | | 10y-2x=5 | | -1[7x+6(x+1)]=-4x-6 | | 2y-30=3y-54 | | (11x-25)+(24+10)=90 | | 3+10b-5-4b= | | 3y+8=y+66 | | -48=5c-2 | | 2x^2-13=11 | | 0.12x+1=0.880 | | 2y=y+50 | | -80=8(7-2x)-(2x-8) | | 11x-4=10x+25 | | 16y-8(3y-2)=-2424 | | 6x+3+87= | | 13y-17+145=180 | | 1.3y-18=2 | | -10+5x=-55 | | 2x=4x-50 | | 2s=s+22 | | 4h-6=7 | | 2t=t+100 | | 3x+7+56= | | 4b=b+33 |